Uderstanding the Concept of Ecosufism: Harmony and the Relationship of God, Nature and Humans in Mystical Philosophy of Ibn Arabi - Syafwan Rozi (Ulumuna, 2019)
This paper examines Ibn Arabi's concept of ecosufism, a new philosophical foundation and paradigma in understanding nature, domination and control over natural resources amidst of global environmental crisis, caused by anthropocentric exploitation towards nature. This ecosufism is related to the constellation of religious orientation amongst monotheism, polytheism and pantheism and the relationship between God and nature in response to the environmental problem. This paper explains Ibn Arabi's philosophical thought on ecology and examines how this notion is based on his Sufi view on the relationship of God, humans and nature. This study shows that Ibn Arabi’s concept of waḥdat al-wujūd (unification of being) and al-insān al-kāmil (perfect human) generate his perception of nature preservation. These two fundamental concepts are relevant to be used as a paradigm for promoting ecosufism, which consider nature as God's manifestation. A perfect human is the one who could realize such a perspective. Protecting nature is necessary because of its position as God's manifestation.